Persistence of Stenotrophomonas maltophilia in Patients with Bacteremia: Incidence, Clinical and Microbiologic Characters, and Outcomes - Sarah Kim; Sehyeon Ji; David Cho; Ahrang Lee; Hae Seong Jeong; Minji Kim; Seong Eun Kim; Kyung-Hwa Park; Sook In Jung; Uh Jin Kim; Sung Un Shin; Seung Ji Kang (Microorganisms)
The risk factors and outcomes associated with persistent Stenotrophomonas maltophilia bacteremia are not well-defined. This retrospective cohort study analyzed 214 cases of S. maltophilia bacteremia diagnosed between 2005 and 2022 at two university hospitals, focusing on the clinical and microbiologic characteristics and outcomes of persistent bacteremia. Persistent S. maltophilia bacteremia, defined as the detection of S. maltophilia for ≥5 days after the initial blood culture, occurred in 25.7% of cases and was significantly associated with mechanical ventilation, polymicrobial infections, and increased 30-day mortality. The early administration of appropriate antibiotics reduced the likelihood of persistence. Isolates from persistent cases demonstrated increased biofilm formation. Molecular typing revealed no specific genotype linked to bacteremia persistence. Resistance to trimethoprim-sulfamethoxazole significantly increased over the study period. Our study offers new insights into the under-explored issue of persistent S. maltophilia bacteremia, a condition that constitutes a notable proportion of bloodstream infections and carries high mortality.